Experimental laboratory design of lime based grouts for masonry consolidation - Luso, Eduarda (2018)
Conservation and strengthening of historic masonry buildings should preserve their significance and ensure their structural stability. The condition of a structure and the extent of the damage determine the type of actions needed. It is important that the selected strategy maintains the existing aesthetic value of the masonry, as well as its structural integrity and the function of components, both during and after any intervention. Grouting is a well-known technique, which can be durable and mechanically efficient, whilst preserving the historic value. The selection of a grout for repair is based on the physical and chemical properties of the existing masonry. Compatibility between the existing and the injection material is a major factor in the success of the intervention. Parameters such as rheology, fluidity, and stability of the mix should be considered to ensure the effectiveness of grout injection. Many commercial ready-mix grouts are available but the use of lime-based grouts formulated in laboratory, with the addition of materials like fly ashes, silica fume, bentonite, hydraulic lime, or metakaolin, have been proposed by different researchers. This article addresses the development of ternary grouts, which show satisfactory mechanical and physical properties, and are viable low-cost alternatives to the commercial grouts.